The close association between dental and periodontal treatments and oral ulcer course in behcet's disease: a prospective clinical study - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER (WILEY-BLACKWELL PUBLISHING, INC, 2009)
The aim of the study was to evaluate the influence of dental and periodontal treatments to the course of oral ulcers in patients with Behcet's disease (BD). Fifty-eight consecutive BD patients with oral ulcers were studied. Twenty-nine patients were in the intervention group (F/M: 15/14, mean age: 39.6 +/- 6.9 years) and 29 (F/M: 15/14, 39.4 +/- 10.6 years) were followed with a conventional treatment approach. In addition to oral hygiene education, dental and periodontal treatments were carried out in the intervention group, whereas the control group was only given oral hygiene education. Patients were evaluated in the pre-treatment observation period (1 month), treatment period (1 month) and 6 months after treatment. An increase in the number of new oral ulcers (4.1 +/- 3.5) was observed within 2 days during the treatment compared with 3-30 days during treatment month (2.3 +/- 1.2) (P = 0.002). However, 6 months after the treatment, the number of oral ulcers (1.9 +/- 1.5) was significantly lower compared with the pre-treatment observation (4.8 +/- 3.2) (P = 0.000) and treatment periods (6.4 +/- 2.3) in the intervention group (P = 0.05), whereas a similar oral ulcer presence was observed in the control group (2.8 +/- 2.4, 3.7 +/- 2.3 and 4.8 +/- 4.3, respectively) (P > 0.05). Dental and periodontal indices were also better in the intervention group during the 6-month follow-up. Our results suggest that, in BD patients, dental and periodontal therapies could be associated with a flare-up of oral ulcers in the short term, but may decrease their number in longer follow-up. They also lead to a better oral health.
Keywords: aphthous ulcerations; oral mucosa; HEAT-SHOCK PROTEINS; INFECTIOUS AGENTS; PATHOGENESIS; HEALTH; ATHEROSCLEROSIS; INDUCTION; SEVERITY; SYMPTOMS; MARKERS